Meta-analysis of the effect of racial discrimination on suicidality. (December 2022) - Coimbra, Bruno Messina; Hoeboer, Chris Maria; Yik, Jutka; Mello, Andrea Feijo; Mello, Marcelo Feijo; Olff, Miranda
Abstract: Racial discrimination (RD) is unfair treatment of individuals based on race or ethnicity. It is a pervasive and increasing phenomenon in the lives of many individuals with deleterious effects on mental health. Research implicates RD in diminished well-being, lower life satisfaction and self-esteem, and mental health disorders. Furthermore, there have been reports that minorities and marginalized groups exposed to RD are at a higher risk of suicide. Given that RD negatively impacts mental health and that suicide is a major public health concern, we meta-analytically reviewed the literature to investigate whether RD is associated with suicidal ideation (SI) and suicide attempt (SA). We identified 43 eligible articles investigating the association between RD and suicidality through PubMed, Embase, PsycINFO and Scopus, from which we pooled 39 effect sizes for SI (58, 629 individuals) and 15 for SA (30, 088 individuals). Results demonstrated that RD has a small but significant effect both on SI ( r  = 0.16, 95% CI: 0.12 to 0.19; p  < 0.0001) and on SA ( r  = 0.13, 95% CI: 0.02 to 0.23; p  = 0.018). We found no indication of publication bias, and fail-safe tests confirmed the robustness of the results. Furthermore, we tested the moderating effects of several study characteristics (e.g., age, race, RD and SI time frame assessment, and categorization of RD measures). The only study characteristic to moderate the effect of RD on SI was SI time frame assessment ( r  = 0.07; 95% CI: 0.015 to 0.12; p  = 0.01). Our findings suggest that SI and SA are phenomena that may be influenced by exposure to RD. Thus, individuals that are discriminated based on race may develop more suicidal thoughts and an increased likelihood of attempting suicide. These findings underscore the need for more prevention and intervention efforts to attenuate the effect of RD on suicidality. Highlights: We conducted a meta-analysis of 62, 349 individuals. We pooled effect sizes from 43 studies from seven countries. Racial discrimination has a statistically significant effect on suicidal ideation ( r  = 0.16, p  < 0.0001). Racial discrimination has a statistically significant effect on suicide attempt ( r  = 0.13, p  = 0.018).